Evaluation of Combining Ability in Stress-Tolerant and Non-Stress Environments for AREX and CIMMYT Maize Inbred Lines - Mhike, Xavier; Lungu, Davies M.; Bindi Vivek (Global Journal of Food and Agribusiness Management, 2024)
Maize (Zea mays L.) is the staple food crop in Zimbabwe with a per capita consumption of 93 kg. It is grown in a wide range of environments with 80% being produced by the smallholder farmers who occupying more than 90% of the marginal areas of the country. Marginal area production has seen a high hybrid turnover on the market hence the need to develop hybrids with stable yields under diverse environments. National program use of inbred lines as testers has had shortcomings in the early identification of good inbred lines, resulting in slow variety development, poor commercial seed production and eventual variety release for farmer use. The objectives of this study were to develop single cross hybrid testers among AREX and CIMMYT lines as well as determine the heterotic relationship among the two sets of inbred lines. In the study, testcross development was done using 10 elite inbred lines each from AREX and CIMMYT programs. Using North Carolina Design II the resultant 100 hybrids were evaluated under optimum and stress (low N and drought) environments. Alpha (0,1) lattice design was used in the evaluation process with traits such as flowering dates, standability, disease scores, plant heights and grain weight being recorded. An across site analysis was done and results showed that there were significant differences (P<0.05) for environments, genotypes and genotype x environment interactions. Significant general combining ability (GCA) effects for all the traits (P<0.05) measured except for plant heights and stem lodging were observed, with five lines being identified as having good (positive) GCA effects for grain yield. Non additive genes were also predominant in most traits except for anthesis dates, anthesis silking interval and ear heights. A total of 39 testcrosses were also assigned heterotic groups basing on the N and SC heterotic groups. Tester identification was based on good GCA for grain yield, stability under diverse environments and maturity of genotype. In the N heterotic group, genotype LT52 (NAW5885/CMML442) was identified as a potential single cross tester in the intermediate maturity group while in the SC heterotic group genotype LT26 (SC5522/ZM621A-BBBB) was identified as another intermediate maturity group tester. In the early maturing category the only possible candidate identified was LT99 (RS61P/CML508) which is in the SC heterotic group. The study also showed that there were heterotic group overlaps of the N and SC groups in relation to CIMMYT’s A and B heterotic groups as some genotype combinations had to be assigned new heterotic groups or had their group unidentified resulting in the need for further evaluation.